2009
DOI: 10.1021/nl803277g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Growth Termination in Controlled Chemical Vapor Deposition Growth of Multiwall Carbon Nanotube Arrays

Abstract: We have investigated growth kinetics of multiwall carbon nanotube (MWCNT) arrays produced by catalytic thermal decomposition of ethylene gas in hydrogen, water, and argon mixture. The MWCNT growth rate exhibits a nonmonotonic dependence on total pressure and reaches a maximum at approximately 750 Torr of total pressure. Water concentrations in excess of 3000 ppm lead to the decrease in the observed growth rate. Optimal pressure and water concentration combination results in a reliable growth of well-aligned MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 26 publications
9
85
0
Order By: Relevance
“…This collective growth picture emerged in contrast to studies that explain CNT forest growth behavior based on mathematical modeling of the behavior of a single catalyst nanoparticle-CNT system. 9,36,87,88 As shown in Fig. 9(b), the mass kinetics exhibit an S-shaped curve, which is fitted by the Gompertz model of population growth.…”
Section: Cnt Growth and Terminationmentioning
confidence: 86%
See 1 more Smart Citation
“…This collective growth picture emerged in contrast to studies that explain CNT forest growth behavior based on mathematical modeling of the behavior of a single catalyst nanoparticle-CNT system. 9,36,87,88 As shown in Fig. 9(b), the mass kinetics exhibit an S-shaped curve, which is fitted by the Gompertz model of population growth.…”
Section: Cnt Growth and Terminationmentioning
confidence: 86%
“…15,34 Moreover, the growth mechanism was shown to shift between tip growth and base growth based on the diameter of the catalyst nanoparticle. 35 Previously, backscatter-electron imaging was used to show that there are no traces of metal nanoparticles on the top of grown CNT forests, 36 to confirm the base-growth process for Fe nanoparticle catalysts on aluminum oxide support layers. The rest of this article will focus on studying this catalyst system.…”
Section: Catalyst Preparation and Treatmentmentioning
confidence: 99%
“…(2009) [9] Carbon nanotube synthesis by fluidized bed chemical vapor deposition [15] CNT synthesis by the CVD process…”
Section: Mwcnt Arraysmentioning
confidence: 99%
“…Stadermann et al [9] presented a quantitative model that showed how accumulation of amorphous carbon patches at the catalyst particle surface and carbon diffusion to the growing nanotube perimeter causes an abrupt growth cessation. In their studies, the effect of partial pressures of ethylene and hydrogen on the driving force for ethylene decomposition was used to explain the nonlinear behavior of the growth rate as shown in Figure 3B.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation